PROBLEMATIKA CALO DALAM PEMBUATAN STNK DI KABUPATEN GOWA PERSPEKTIF SIYASAH SYAR’IYYAH - Rezeki, Mugiasih; Mustafa, Adriana (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2020)
The use of broker in making STNK, we must look at the Islamic State administration law, as well as how the view of fuqaha in terms of brokering practices, and how the Qur'an and Hadits explain it, as was known in the time of the Prophet Muhammad STNK did not yet exist, that is because at the time of the Apostles people still used horses and camels in traveling, while regarding motor vehicles in the time of the apostles, there were none, only brokering services at the time of the apostles had but, only on the buying and selling shutter. This study raises the issue regarding the position of brokers in making STNK in Gowa Regency, and the causes and Siyasah Syar'iyyah Perspectives concerning brokers. It is expected that Samsat Gowa can understand its duty in serving the interests of the community and also Samsat Gowa will be even harder in conducting socialization in the community, and in this case the Samsat can take decisive action for principals who become broker in order to minimize the public not to use broker in making vehicle registration